Molecular phylogenetics reveal multiple tertiary vicariance origins of the African rain forest trees (2008)
Background Tropical rain forests are the most diverse terrestrial ecosystems on the planet. How this diversity evolved remains largely unexplained. In Africa, rain forests are situated in two geographically isolated regions: the West-Central Guineo-Congolian region and the coastal and montane regions of East Africa. These regions have strong floristic affinities with each other, suggesting a former connection via an Eocene pan-African rain forest. High levels of endemism observed in both regions have been hypothesized to be the result of either 1) a single break-up followed by a long isolation or 2) multiple fragmentation and reconnection since the Oligocene. To test these hypotheses the evolutionary history of endemic taxa within a rain forest restricted African lineage of the plant family Annonaceae was studied. Molecular phylogenies and divergence dates were estimated using a Bayesian relaxed uncorrelated molecular clock assumption accounting for both calibration and phylogenetic uncertainties. Results Our results provide strong evidence that East African endemic lineages of Annonaceae have multiple origins dated to significantly different times spanning the Oligocene and Miocene epochs. Moreover, these successive origins (c. 33, 16 and 8 million years – Myr) coincide with known periods of aridification and geological activity in Africa that would have recurrently isolated the Guineo-Congolian rain forest from the East African one. All East African taxa were found to have diversified prior to Pleistocene times. Conclusion Molecular phylogenetic dating analyses of this large pan-African clade of Annonaceae unravels an interesting pattern of diversification for rain forest restricted trees co-occurring in West/Central and East African rain forests. Our results suggest that repeated reconnections between the West/Central and East African rain forest blocks allowed for biotic exchange while the break-ups induced speciation via vicariance, enhancing the levels of endemicity. These results provide an explanation for present day distribution patterns and origins of endemicity for African rain forest trees. Moreover, given the pre-Pleistocene origins of all the studied endemic East African genera and species, these results also offer important insights for setting conservation priorities in these highly diversified but threatened ecosystems.